W krolewskiej sluzbie : wspomnienia kamerdynera ksienej Diany - Burrell, Paul, 1958- (Warszawa : Magnum, 2004)
Polish translation of "Royal Duty". The biography of the Princess Diana by her servant and close friend Paul Burrell.
Keywords: Diana, -- Princess of Wales, -- 1961-1997.; Burrell, Paul, -- 1958-; Princesses -- Great Britain -- Biography